2014
DOI: 10.1097/adm.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Noncompliance With Buprenorphine Maintenance Treatment

Abstract: Patients found to be noncompliant were more likely to suffer from comorbid psychiatric illness. Patients who tested positive for benzodiazepines or cannabis were more likely to be noncompliant with treatment. Although the rate of noncompliance (inaccurate pill count) was high, patients were still found to be taking their prescribed buprenorphine as evidenced by positive UDS for buprenorphine/norbuprenorphine. In addition, our sample had a high rate of negative UDS screens for opioids and cocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…(Fareed et al, 2014; Ferri, Finlayson, Wang, & Martin, 2014; Hser et al, 2014) Illicit buprenorphine use at OBOT enrollment is associated with increased short-term retention in buprenorphine treatment. (Alford et al, 2011; Cunningham, Roose, Starrels, Giovanniello, & Sohler, 2013) Once enrolled in OBOT, illicit benzodiazepine(Ferri et al, 2014) and illicit opioid (Fiellin et al, 2008; Stein, Patricia Cioe, & Friedmann, 2005) use early in treatment are both predictive of short-term disengagement.…”
Section: 0 Introductionmentioning
confidence: 99%
“…(Fareed et al, 2014; Ferri, Finlayson, Wang, & Martin, 2014; Hser et al, 2014) Illicit buprenorphine use at OBOT enrollment is associated with increased short-term retention in buprenorphine treatment. (Alford et al, 2011; Cunningham, Roose, Starrels, Giovanniello, & Sohler, 2013) Once enrolled in OBOT, illicit benzodiazepine(Ferri et al, 2014) and illicit opioid (Fiellin et al, 2008; Stein, Patricia Cioe, & Friedmann, 2005) use early in treatment are both predictive of short-term disengagement.…”
Section: 0 Introductionmentioning
confidence: 99%
“…MAT patients with co-occurring disorders have more severe psychiatric, medical, and legal problems at intake 810 and post-treatment, and are at higher risk for relapse and treatment noncompliance. 8,1012 Though MAT patients with co-occurring disorders are more severe at intake 8,9 and have more severe psychiatric problems after release, 9,11 some studies have found these patients to have equivalent or better substance use outcomes, 9 including longer treatment retention 13,14 and lower relapse rates. 10 Researchers have hypothesized that increased psychiatric severity may motivate patients to seek and remain in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The lead author (J.B.) sketched together a set of variables that were important in determining the severity of need, loosely based on the Addiction Severity Index (ASI; McLellan et al, 2006). Further refinements based on clinical expertise and reviews of the scientific literature (eg, Sullivan et al, 2010; Bukten and Skurtveit, 2014; Fareed et al, 2014; Perrault et al, 2015) led to a brief 21-item screener. It assesses areas of psychosocial functioning (eg, legal, drug and alcohol use, transportation, chronic pain, social support) with individual items summed for a possible maximum score possible of 26 (Fig.…”
Section: Methodsmentioning
confidence: 99%